THE PREVALENCE AND THE MORPHOLOGICAL ASPECTS OF THE ONODI CELLS – COMPUTER TOMOGRAPHIC STUDY - Alin Horatiu Nedelcu; Cosmin Gabriel Popa; Simona Alice Partene Vicoleanu; Razvan Tudor Tepordei; Gabriel Statescu; Roxana-Andreea Popa; Marius Constantin Moraru; Manuela Ursaru (Romanian Journal of Oral Rehabilitation)
Introduction: Onodi cells represent the abnormal migration of posterior ethmoidal cells into the sphenoid sinus cavity. This migration can be unilateral or bilateral. Moreover, a single cell or several ethmoid cells may be involved, hence the identification of the two morphological types, unilocular and multilocular, respectively. The aim of this study is to evaluate the prevalence of the Onodi cells in the Romanian population, to investigate the encountered morphological types and to assess their distribution based on the gender and placement. Finally yet important, we intend to investigate the causal relationship between the presence of the Onodi cells and chronic rhinosinusitis. Materials and Methods: Our retrospective study analyses 121 cranio-cerebral computed tomography (CT) datasets. Two expert radiologists independently investigated the images using RadiAnt DICOM Viewer software. The uncertain cases were later resolved by consensus. Results: In 58 (47.93%) of 121 cases, we identified the presence of Onodi cells. No significant statistical difference was demonstrated regarding gender. With regard to the morphological forms, we recorded the preponderance of the unilocular type (63 out of 84 cases, 75%) compared to the multilocular type (21 out of 84 cases, 25%). Discussions and Conclusions: Onodi cells have a high prevalence in the studied cohort, showing no predisposition related to sex or location. After implementing statistical methods, we demonstrated that there is no causal relationship between the presence of Onodi cells and chronic rhinosinusitis.